Increasing Student Learning Interest with Multiple Modeling Techniques - Ulfa, Maria; Nurdendis, La Ode (Jurnal Bimbingan dan Konseling Terapan, 2023)
The lack of attention and interest of students, not wanting to be involved, and not being happy to participate in the learning process can be seen in the attitudes and behavior of students, indicating the low interest in student learning. This is the basis for this research. Therefore this study aims to increase students' interest in learning with multiple modeling techniques through group guidance services. A quantitative approach with the pre-experimental method through the one group pretest posttest design was used in this study. The population used was class VIII students of SMP Negeri 2 Kadatua with a total of 28 students and used a sampling technique through purposive sampling with a sample size of 12 students who had low interest in learning based on the pretest results. The data collection technique uses a learning interest scale and is analyzed through the Wilcoxon test statistical analysis. The result of this research test is an increase in students' interest in learning after giving multiple modeling techniques with a score of 378 or 31.5%. The results of this study were also proven through a significant Wilcoxon test analysis of 0.002, it was concluded that the multiple model technique through group guidance services was effective in increasing student learning interest.